2012
DOI: 10.1021/es301261x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Disturbance of Element Cycles at the Earth’s Surface

Abstract: 9The extent to which humans are modifying Earth's surface chemistry can be quantified by antimony, platinum, palladium, rhenium, rhodium and chromium currently exceed natural fluxes. 21For these elements mining is the major factor of anthropogenic influence, whereas petroleum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 59 publications
4
125
2
1
Order By: Relevance
“…Since US coal production is about 10% of the global coal production, we estimate that the global V flux to the hydrosphere through effluent release is about 2.8 × 10 9 g V/y. Recent studies have indicated (88), except for V (this paper) and Hg (107,108). All data in 10 9 grams per year.…”
Section: Significancementioning
confidence: 73%
“…Since US coal production is about 10% of the global coal production, we estimate that the global V flux to the hydrosphere through effluent release is about 2.8 × 10 9 g V/y. Recent studies have indicated (88), except for V (this paper) and Hg (107,108). All data in 10 9 grams per year.…”
Section: Significancementioning
confidence: 73%
“…Human activities such as mining and construction activities can significantly disturb the natural flow of elements between major ecosystem reservoirs and alter the physical and chemical processes at the Earth's surface (Sen and Peucker-Ehrenbrink 2012). It is widely recognized that mining activities for rare earth ores have changed the environmental conditions, causing serious environmental problems such as permanent damages to ecosystems, severe soil erosion, air pollution, and loss of biodiversity (Salomons 1995;Aguilar et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple human activities release contaminants to the biosphere, and those emissions have dramatically increased since the industrial revolution (Ng and Patterson 1982;Nriagu 1996;Sen and Peucker-Ehrenbrink 2012). Impacts of these emissions on the environment have been extensive, including elevated levels of trace elements in air, surface waters, and terrestrial and lacustrine sediments-both in industrialized and remote uninhabited locations, primarily via aeolian deposition (Nriagu and Pacyna 1988;Boutron et al 1995;Boyle et al 2005).…”
Section: Introduction Environmental Impacts Of Contaminant Emissionsmentioning
confidence: 99%